The mediating effect of organizational and co-workers support on employee retention in international non-governmental organizations in Gaza Strip - Nassar, Samia; Hossain, Md Billal; Tóth Naárné, Éva Zsuzsanna; Vasa, Laszlo (Decision Making: Applications in Management and Engineering, 2022)
Because of the enormous beneficial influence that employee retention has on work-related outcomes, it has been the focus of much research for a long time and especially in the field of International Non-Governmental Organizations (INGOs). The importance of highlighting elements that may enhance the beneficial effect of Workplace Fun (WF) and Work-Life Balance (WLB) in increasing employee retention (ER). So this research examines the influence of worklife balance and workplace fun on employee retention, as well as the mediating effect of Perceived Organizational Support (POS) and Perceived Coworker Support (PCS) on employee retention. The obtained data were analyzed using a conceptual model. An online survey was used to collect the information. More than 358 surveys and analyses have been conducted utilizing the AMOS. In terms of employee retention, the study found a favorable correlation between workplace fun and work-life balance. The association between workplace fun, work-life balance, and employee retention was mediated by supervisor and coworker support. To assist firms to recognize the value of supervisor support in minimizing bad work outcomes for employees, these findings will be useful.